Effects of chronic cadmium exposure on the sexual maturity, production and bioaccumulation of pearl gourani trichogaster leeri - Ibrahim, Al-Switi; Kabbashi, Nassereldeen Ahmed (Academy of Agricultural Sciences, NAAS, India, 2003)
80 day bioassay using three concentration of Cadmium 0.420, 0.201 and 0.121 mg/L were conducted beginning with 5-6 day old Gourami Trichogaster Leeri. The uptake of cadmium occurred during pregnancy indicating that females transfer cadmium to the embryo. Highest concentration of cadmium occurred in 5 day old concentration (mg/g) which then declined with growth. Cadmium burden (mg/fish) increased primarily from 28-45 day of bioassay. Gourami exposed to 0.201 and 0.121 mg/L cadmium for 45 day had similar cadmium concentration as in control. The most sensitive indicator of toxicity was sexual maturity, which can be used as an estimator of chronic toxicity.